Peran Kecemasan dengan Prokrastinasi Akademik pada Mahasiswa Psikologi yang Sedang Menempuh Skripsi: Indonesia - Maria Vania Tertianing Nugroho (Interaktif : Jurnal Ilmu-Ilmu Sosial, 2024)
The aim of this research is to see how big a role anxiety plays in influencing procrastination. The sample for this research was 157 Psychology students at Brawijaya University who were working on their thesis using the correlational method and research sampling was carried out using convenience sampling with predetermined criteria. The measuring instruments used are the Anxiety Symptoms Questionnaire to measure anxiety and the Thesis Writing Procrastination Scale (TWPS) to measure academic procrastination. Research analysis was carried out using a simple linear regression analysis method to obtain final quantitative analysis results. The results of the research state that there is a role of anxiety in academic procrastination in Brawijaya University psychology students who are working on their thesis. The results of the study show that there is a positive influence of anxiety on procrastination in students who are working on their thesis with a significance of 0.001 (<0.05) and R² 0.63 Keywords: Anxiety, Procrastination, Undergraduate Thesis, Academic Procrastination